Association of neck circumference with general and abdominal obesity in children and adolescents: the weight disorders survey of the CASPIAN-IV study. Issue 9 (30th September 2016) - Kelishadi, Roya; Djalalinia, Shirin; Motlagh, Mohammad Esmaiel; Rahimi, Ali; Bahreynian, Maryam; Arefirad, Tahereh; Ardalan, Gelayol; Safiri, Saeid; Hasani, Motahare; Asayesh, Hamid; Mansourian, Morteza; Qorbani, Mostafa
Abstract : Objectives: This study aimed to evaluate the association of neck circumference (NC) with obesity to determine the sex-specific and age-specific optimal cut-off points of this measure in association with obesity in a national sample of the Iranian paediatric population. Methods: This survey on weight disorders was conducted among a national sample of Iranian children and adolescents, aged 6–18 years. Using the area under the curve (AUC) of the receiver operator characteristic curves, we evaluated the association of NC with general and abdominal obesity. Results: This national survey was conducted among 23 043 school students (50.8% boys) with a mean age (SD) of 12.55 (3.31) years. A significant association was documented between NC and other anthropometric measures in both sexes and in the whole population. In all age groups and genders, NC performed relatively well in classifying participants to overweight (AUC: 0.67 to 0.75, p<0.001), general obesity (AUC: 0.81 to 0.85, p<0.001) and abdominal obesity (AUC: 0.73 to 0.78, p<0.001). Conclusions: NC can be considered as a simple time-saving clinical tool for obesity detection in large population-based studies in children and adolescents. It is significantly correlated with indices of adiposity and can reliably identify children with general and abdominal obesity in the Iranian paediatric population.